HIV and the risk of direct obstetric complications: a systematic review and meta-analysis. - Clara Calvert; Carine Ronsmans (PLoS ONE, 2013)
Background Women of reproductive age in parts of sub-Saharan Africa are faced both with high levels of HIV and the threat of dying from the direct complications of pregnancy. Clinicians practicing in such settings have reported a high incidence of direct obstetric complications among HIV-infected women, but the evidence supporting this is unclear. The aim of this systematic review is to establish whether HIV-infected women are at increased risk of direct obstetric complications. Methods and findings Studies comparing the frequency of obstetric haemorrhage, hypertensive disorders of pregnancy, dystocia and intrauterine infections in HIV-infected and uninfected women were identified. Summary estimates of the odds ratio (OR) for the association between HIV and each obstetric complication were calculated through meta-analyses. In total, 44 studies were included providing 66 data sets; 17 on haemorrhage, 19 on hypertensive disorders, five on dystocia and 25 on intrauterine infections. Meta-analysis of the OR from studies including vaginal deliveries indicated that HIV-infected women had over three times the risk of a puerperal sepsis compared with HIV-uninfected women [pooled OR: 3.43, 95% confidence interval (CI): 2.00-5.85]; this figure increased to nearly six amongst studies only including women who delivered by caesarean (pooled OR: 5.81, 95% CI: 2.42-13.97). For other obstetric complications the evidence was weak and inconsistent. Conclusions The higher risk of intrauterine infections in HIV-infected pregnant and postpartum women may require targeted strategies involving the prophylactic use of antibiotics during labour. However, as the huge excess of pregnancy-related mortality in HIV-infected women is unlikely to be due to a higher risk of direct obstetric complications, reducing this mortality will require non obstetric interventions involving access to ART in both pregnant and non-pregnant women.